Innovation in food engineering : new techniques and products - Passos, Maria Laura; Ribeiro, Claudio P. (Contemporary food engineering, 2010)
Offers an overview of modern processing technologies. This book highlights their use to develop food products and ingredients that meet consumers increased demands for quality and safety. Each chapter in the Innovative Techniques section begins with a review of the fundamentals of the new or modified technique, its advantages, and results.